Synthesis of Mesoporous In₂O₃ Nanocubes for H₂ Gas Sensor Applications - Pham, Van Tong; Luu, Hoang Minh; Bui, Quang Thanh; Chu, Manh Hung (Old Journal, 2020)
Mesoporous In₂O₃ nanocubes were synthesized through a simple, low-cost hydrothermal method without using soft template, followed by calcination. The morphology and crystal structure of the In₂O₃ nanocubes were examined by scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray diffraction (XRD). The gas sensors were fabricated by drop casting method and tested over flammable and explosive H₂ gas at different temperatures. The best performance was found at working temperature of 350oC with the highest response of 2.3 to 1000 ppm H₂. The sensor showed fast response/recovery time (5 s/45 s), and good stability after six consecutive measurement cycles.